1999
DOI: 10.1176/ajp.156.10.1608
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primary Dysthymia With Group Cognitive Therapy and Pharmacotherapy: Clinical Symptoms and Functional Impairments

Abstract: Sertraline treatment effectively reduces the clinical symptoms and functional impairments associated with dysthymia. Although the group cognitive behavior therapy intervention was less effective in alleviating clinical symptoms, it augmented the effects of sertraline with respect to some functional changes, and in a subgroup of patients it attenuated the functional impairments characteristic of dysthymia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 67 publications
2
77
0
10
Order By: Relevance
“…[19][20][21] As such, the lack of controlled studies comparing the relative efficacy of psychotherapy and pharmacotherapy (either alone or in combination) is surprising. It was recently reported, however, that in the short-run, pharmacotherapy (using a selective serotonin reuptake inhibitor) was more efficacious than group cognitive behavior therapy (CBT) in alleviating symptoms of dysthymia, 22 although CBT attenuated several functional aspects of the illness. Using a somewhat more protracted regimen (16 weeks), CBT was effective in a study involving a small number of dysthymic subjects.…”
Section: Dysthymia: Clinical and Epidemiological Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21] As such, the lack of controlled studies comparing the relative efficacy of psychotherapy and pharmacotherapy (either alone or in combination) is surprising. It was recently reported, however, that in the short-run, pharmacotherapy (using a selective serotonin reuptake inhibitor) was more efficacious than group cognitive behavior therapy (CBT) in alleviating symptoms of dysthymia, 22 although CBT attenuated several functional aspects of the illness. Using a somewhat more protracted regimen (16 weeks), CBT was effective in a study involving a small number of dysthymic subjects.…”
Section: Dysthymia: Clinical and Epidemiological Featuresmentioning
confidence: 99%
“…Moreover, it has been suggested that optimal drug effects would be obtained when administered primarily to patients with subaffective, rather than character spectrum disorder. 4 In fact, studies which employed rigorous diagnostic criteria, established the efficacy of tricyclic agents, such as imipramine and desipramine, [131][132][133][134][135][136][137] MAOIs, 136,138,139 the reversible monoamine oxidase inhibitor, moclobemide, 114,137,[140][141][142][143] SSRIs, such as fluoxetine and sertraline, 22,23,111,132,134,[144][145][146] as well as other agents, such Molecular Psychiatry as the 5HT 2 antagonist, ritanserin, 147,148 the selective norepinephrine reuptake inhibitor, reboxetine, 149 and the serotonin/norepinephrine reuptake inhibitor (SNRI), venlafaxine 150,151 (Table 1). The use of well tolerated compounds, including moclobemide and sertraline, may be effective in the long-term management of dysthymia.…”
Section: Pharmacological Contributions To the Analysis Of Dysthymiamentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos mostram que 50 a 60% dos pacientes com distimia respondem ao tratamento com antidepressivos 61,62 . Os inibidores da monoamino-oxidase (IMAO), os antidepressivos tricíclicos (ADT) e ISRS são eficazes no tratamento da distimia 40,61,63,64 .…”
Section: Comorbidade Com O Transtorno Depressivo Maiorunclassified
“…Os inibidores da monoamino-oxidase (IMAO), os antidepressivos tricíclicos (ADT) e ISRS são eficazes no tratamento da distimia 40,61,63,64 . Manipulações e reposições hormonais ainda carecem de estudos 65,66 .…”
Section: Comorbidade Com O Transtorno Depressivo Maiorunclassified